2020
DOI: 10.1051/kmae/2020025
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate colonisation associated with native and invasive leaf litter decomposition

Abstract: Lake and reservoir ecosystems are regarded as heterotrophic detritus-based habitats which are dependent on both autochthonous and allochthonous organic matter for the majority of energy inputs. In particular, allochthonous detritus is in particular important for the trophic dynamics of microbial organisms, macroinvertebrates and benthic plants in freshwaters. Here, we assess macroinvertebrate colonisation, and quantify decomposition rates, of leaf litter from species of native and invasive plants in a small ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The outcomes of this study suggest that certain invasive litter inputs into freshwater may contribute to dynamic interactions among invasion, invertebrate and microorganism colonization, and nutrient cycling [24]. Nutrient-rich leaf litter such as L. camara decomposes faster due to low concentrations of defensive compounds such as lignin [43].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The outcomes of this study suggest that certain invasive litter inputs into freshwater may contribute to dynamic interactions among invasion, invertebrate and microorganism colonization, and nutrient cycling [24]. Nutrient-rich leaf litter such as L. camara decomposes faster due to low concentrations of defensive compounds such as lignin [43].…”
Section: Discussionmentioning
confidence: 91%
“…In this study, whilst we demonstrated that interspecific differences in leaf litter decomposition are important for allochthonous nutrient dynamics within freshwater environments, these differences were not conserved and thus generalizable according to alien-native statuses. Native decomposers have been previously posited to be more efficient in colonizing native leaf litter over alien leaves (but see [24]), owing to co-evolutionary backgrounds among species [38]. As such, higher nutrient release is to be generally expected from native species, at least in the short-term.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such basal position implies an important relationship with ecosystem components. Firstly, macroinvertebrate assemblages can have an important influence on numerous processes [56], such as nutrient cycles [57, 58, 59], primary productivity [60], decomposition [61, 62, 63], and translocation of materials [64, 65]. Then, they are an important resource for organisms belonging to higher trophic levels such as fish species.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial number of allelochemicals were identified in the L. camara leaves (Table 2). In addition, the decomposition rate of L. camara litter was faster than that of the leaf litter of native plant species [68]. In fact, lantadene A and lantadene B, which were isolated from the leaves, were also found in the rhizosphere soil of L. camara over growthinhibitory levels [58].…”
Section: Invasion and Allelopathy Of L Camaramentioning
confidence: 95%